Kedwibahasaan Anak Sekolah Dasar dan Implikasinya terhadap Pembelajaran Bahasa Indonesia di Kelas IV - Sukmawaty, Sukmawaty; Firman, Firman; T, Fatimah; Mirnawati, Mirnawati; Rustan, Edhy; Guntur, Muhammad (Nuances of Indonesian Language, 2024)
This research explores bilingualism among fourth-grade students at SDN 42 Buntu Sarek, focusing on Luwu-Indonesian conversations. Utilizing a qualitative descriptive method with observation, interviews, and documentation as data collection techniques, the study reveals the complex dynamics of bilingualism within and outside the classroom. Inside the classroom, students predominantly use Indonesian for formal interactions, while outside the classroom, Luwu language dominates informal social interactions. Environmental factors, including family, peers, and media, play a significant role in shaping students' speech patterns. The use of a mixed language has a positive impact on language skills development, enriching vocabulary. However, challenges arise in deepening proficiency in one language, leading to potential identity doubts, particularly in formal Indonesian contexts. Addressing these challenges requires educational strategies supporting understanding and language skill development in both languages.